(untitled) (Sains Humanika, 2023)
Previous research has demonstrated that since 1967, the Malaysian government has set a target percentage rate of 60:40 for student involvement in the science stream compared to literature. This ratio policy has been followed throughout the national school system ever since. However, such a ratio appears to be impossible to maintain year after year. Therefore, the empowerment of science education needs to be explored from an earlier. This study was conducted to (i) explore best practices in Early Science in relation to the implementation of STEM activity in preschool; (ii) explore best practices in Early Mathematics in relation to the implementation of STEM activity in preschool; (iii) explore technology-assisted teaching tools in relation to the implementation of STEM activity in preschool; and (iv) explore engineering activity in relation to the implementation of STEM activity in preschool. This qualitative study employed a case study approach, with data triangulation based on interviews, observations, and document analysis serving as the exploratory method. This study was conducted independently in three Malaysian preschools in Perak and Selangor respectively, with four teachers and 39 children participating as study participants. ATLAS.ti version 8 software was used to generate, arrange, and organise the themes from the three research instruments described utilizing descriptive analysis with the flow of coding processes. The results show that there are nine STEM education best practices, with play-based learning being identified by participants the most frequently. Thus, this study’s most significant contribution is the potential to bridge the gap between the Ministry of Education Malaysia’s goals to advance STEM education globally, starting in the early years.